The effect of gefapixant, a P2X3 antagonist, on cough reflex sensitivity: a randomised placebo-controlled study. Issue 1 (4th July 2019) - Morice, Alyn H.; Kitt, Michael M.; Ford, Anthony P.; Tershakovec, Andrew M.; Wu, Wen-Chi; Brindle, Kayleigh; Thompson, Rachel; Thackray-Nocera, Susannah; Wright, Caroline
We evaluated the effect of gefapixant on cough reflex sensitivity to evoked tussive challenge. In this phase 2, double-blind, two-period study, patients with chronic cough (CC) and healthy volunteers (HV) were randomised to single-dose gefapixant 100 mg or placebo in a crossover fashion. Sequential inhalational challenges with ATP, citric acid, capsaicin and distilled water were performed 1,  3 and 5 h after dosing. Mean concentrations evoking ≥2 coughs (C2) and ≥5 coughs (C5) post dose versus baseline were co-primary endpoints. Objective cough frequency (coughs·h −1 ) over 24 h and a cough severity visual analogue scale (VAS) were assessed in CC patients. Adverse events were monitored. 24 CC patients and 12 HV were randomised (mean age 61 and 38 years, respectively). The cough challenge threshold increased for ATP by 4.7-fold (C2, p≤0.001) and 3.7-fold (C5, p=0.007) for gefapixant versus placebo in CC patients; in HV, C2 and C5 increased 2.4-fold (C2, p=0.113; C5, p=0.003). The distilled water C2 and C5 thresholds increased significantly (p<0.001) by a factor of 1.4 and 1.3, respectively, in CC patients. Gefapixant had no effect on capsaicin or citric acid challenge. Median cough frequency was reduced by 42% and the least squares mean cough severity VAS was 18.0 mm lower for gefapixant versus placebo in CC patients. Dysgeusia was the most frequent adverse event (75% of HV and 67% of CC patients). ATP-evoked cough was significantly inhibited by gefapixant 100 mg, demonstrating peripheral target engagement. Cough count and severity were reduced in CC patients. Distilled water may also evoke cough through a purinergic pathway. Gefapixant reduces coughing in patients and blocks ATP- and distilled-water-induced cough, but not cough evoked by citric acid or capsaicin, suggesting a unique TRPV4/ATP pathway may underlie cough hypersensitivity seen in chronic refractory cough http://bit.ly/2Gcr9Lr